Spectral Studies on the Interaction of Sanguinarine Chloride with Cytidine - Bin Zhang, Jian; Peng Du, Zuo; Zhang, Tong; Hui Wei, Xiong (Asian Journal of Chemistry, 2011)
In this work, the interaction of sanguinarine chloride (SAN) with cytidine at physiological pH 7.2 was investigated with the help of UV-visible, fluorescence, 1H NMR spectral measurements and thermodynamic calculations. It was found that the interaction between sanguinarine chloride and cytinde results in hypochromism and red shift of the sanguinarine chloride E absorption band (274 nm) and one sanguinarine chloride molecule can bind with two cytidine molecules with the binding constant in the order of 107, indicating that the binding of sanguinarine chloride with cytidine is not only exothermic but entropy-driven with DrHmQ = - 4.87 kJ mol-1, DrSmQ = 0.13 kJ mol-1 K-1 and DrGmQ = - 44.45 kJ mol-1 at 298.15 K.